Ewaluacja i wskaźniki w cyklu planowania i realizacji polityk publicznych - Górniak, Jarosław; Keler, Karolina (Journal of Public Governance, 2008)
The purpose of the article is to present the functions of evaluation and indicators in a public policy cycle, as well as discuss problems related to the execution of those functions. In particular, policy formulation and evaluation phases as well as measurement of programs’ effects via indicators are taken into consideration. The first part includes a detailed description of the functions of diagnosis, indicators and evaluation in a public policy cycle. The second part of the paper outlines evaluation and the utilization of indicators at the evaluation stage of the cycle. The part concludes with a discussion of theory-driven evaluation and the significance of measuring net effects for the identification of causal impacts of a given intervention. The authors believe that we should treat as results all the intended effects of a given intervention (program, policy) for ultimate beneficiaries, regardless of when they occur, whether they are immediate or delayed, whereas impacts should be construed as intended and unintended effects for the broader system in which problems have arisen (the European Commission considers delayed results as impacts). Difficulties related to the measurement of impacts of an intervention impact are also discussed. The authors note that obtaining measurable results is a necessary condition for any impact of the intervention to take place. In the third part of the article, the authors discuss the role of indicators and evaluation in public policy formulation. Special attention is drawn to the need for a proper definition of objectives and the choice of relevant indicators in the process of public policy formulation. The authors underscore the fact that there exist considerable differences in defining purposes or intentions as goals, objectives and targets. The paper also discussed problems related to the setting of target values for indicators as well as the relationships among the measurement of outputs, results, and impacts of an intervention. In conclusion, the authors emphasize that evaluation and indicators can constitute useful tools in conducting public policies, but putting them into practice requires coping with problems discussed in the article.